Common notions and composite collaborations: Thinking with Spinoza to design urban infrastructures for human and wild cohabitants - Ruddick, Sue (Interstices: Journal of Architecture and Related Arts, 2021)
This paper explores the ways in which we might construct urban environments that are responsible to the needs of more than just human cohabitants. Drawing on Spinoza’s common notion and attentive to the possibilities of socio-natures that both construct and respond to the habitat needs of urban wildlife, I look at how urban design and wildlife habitat might be thought and planned together as a human/non-human composite, invoking a complex spatial and temporal choreography which serves divergent needs. Drawing on examples of urban design in Toronto, Canada, this paper offers a way to think of the city as a composite body in Spinoza’s terms, to become open to an awareness of the city as a composition of forces—a choreography of bodies that are constantly interweaving and overflowing imagined boundaries, struggles that are fought as much over time as space, the accommodation of the temporalities and spatialities of other life processes, other rhythms and cycles that would, without a recalibration, sync uneasily with the pacing and spacing of human requirements.